STREET MATHEMATICS AND SCHOOL MATHEMATICS (Authors: Terezinha Nunes, Analucia Dias Schliemann, & David William Carraher) - Riggs, Howard (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1994)
Terezinha Nunes, Analucia Dias Schliemann, & David William Carraher. STREET MATHEMATICS AND SCHOOL MATHEMATICS. London: Cambridge University Press (1993). 170 pp. $49.95 cloth (ISSN 0-521-38116-9) $16.95 paper (ISSN 0-521-38813-9).